2017
DOI: 10.1177/0269215517718367
|View full text |Cite
|
Sign up to set email alerts
|

Is the effect of coping styles disease specific? Relationships with emotional distress and quality of life in acquired brain injury and multiple sclerosis

Abstract: In both patient groups, coping patterns are similar, and emotion-oriented coping negatively influences quality of life. Additionally, in multiple sclerosis, seeking emotional support and distraction (CISS-A) was positively associated with quality of life. Interventions to improve adaptive coping could be organized within a neurorehabilitation setting for both patient groups together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…ing and anxiety in the final analyses. The importance of coping in quality of life and in anxiety is stated in multiple MS studies 18,24,49. Our study confirms this pattern and is the first MS study on anxiety that includes demographic, disease-related and psychological variables in a multivariable analysis, including comprehensive cognitive functioning.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…ing and anxiety in the final analyses. The importance of coping in quality of life and in anxiety is stated in multiple MS studies 18,24,49. Our study confirms this pattern and is the first MS study on anxiety that includes demographic, disease-related and psychological variables in a multivariable analysis, including comprehensive cognitive functioning.…”
supporting
confidence: 85%
“…The importance of coping in quality of life and in anxiety is stated in multiple MS studies. 18,24,49 More specifically, a greater reliance on emotion-focused coping strategies is related to poor psychosocial adjustment, depression and anxiety. 49 Lack of correlations between these disease-related variables, together with the strong relation between anxiety, depression and cognitive complaints, can possibly be explained by coping as a moderating variable.…”
Section: Ta B L E 2 Means and Standard Deviations Of Psychological Qumentioning
confidence: 99%
See 1 more Smart Citation
“…Specific coping styles (e.g. emotion-oriented coping) have even been reported to have an effect on disease severity, for example in multiple sclerosis (Brands et al 2017). For CSC, several mostly small-sized studies have reported an association between severe psychosocial stressful events and the onset of disease, with one study describing this association especially in patients with poor coping mechanisms (Conrad et al 2000;Spahn et al 2004;Lahousen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…LiSAT-9 is a potential life satisfaction instrument of choice in studies assessing quality of life in patients with MS, acquired brain or spinal cord injury where spasticity is a major concern [24, 34]. A decreased health-related quality of life in the elderly due to the presence of comorbid diseases, impaired mobility, social isolation, depressed feelings and moods among others has been studied [35].…”
Section: Discussionmentioning
confidence: 99%